(Un)Digital Poland: The Gap in the Digital Skills of Human Capital - Katarzyna Śledziewska; Renata Włoch (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Kotor, Montengero, 10-11 September 2015, 2015)
The aim of the paper is to present data concerning the current gap in the digital competences of human capital in Poland in comparison to other EU countries. To this end we use data from the Digital Economy and Society Index (DESI) and Eurostat. The data show that computer and Internet skills amongst Poles are significantly lower than the skills of other Europeans, including those from other new EU member states. We argue that the gap in human digital skills is the major cause of the low level of digitalisation of the Polish economy as a whole, which may critically impair its development prospects in the context of the EU Digital Single Market.
Keywords: O; 330; digitalisation; digital skills; human capital; digital economy